2021
DOI: 10.18510/hssr.2021.925
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Social Media Uses, Internet Mediation and Political Participation in Pakistan

Abstract: Purpose of the study: This study explores the relationship between internet connectivity, social media usage, and political participation. Besides, assess the connection between political participation and vote casting behaviour on social media. Methodology: The researchers used the Uses and Gratification theory and adopted a quantitative method to collect people's views. A designed questionnaire disseminates among 375 male and female Gujrat and Chi-Square analyses conducted on respondents' data. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Access to tangible digital tools is a prerequisite to maximizing the affordances of social media to facilitate political participation. We coined these prerequisites to SMPP as digital profile , which includes having active accounts on one or more social media sites (Effing et al, 2011 ; Abdu et al, 2017 ; Albu and Etter, 2018 ), ownership of one or more gadgets (Schradie, 2011 ; Kim et al, 2016 ; Lin and Chiang, 2017 ), and internet connection (Wang et al, 2018 ; Shehzad et al, 2021 ). For the second research objective of the study, we will determine how the respondents' digital profile influences their SMPP-GI.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to tangible digital tools is a prerequisite to maximizing the affordances of social media to facilitate political participation. We coined these prerequisites to SMPP as digital profile , which includes having active accounts on one or more social media sites (Effing et al, 2011 ; Abdu et al, 2017 ; Albu and Etter, 2018 ), ownership of one or more gadgets (Schradie, 2011 ; Kim et al, 2016 ; Lin and Chiang, 2017 ), and internet connection (Wang et al, 2018 ; Shehzad et al, 2021 ). For the second research objective of the study, we will determine how the respondents' digital profile influences their SMPP-GI.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…A wealth of research has indicated the positive influence of social media use on political participation (Dimitrova and Bystrom, 2013 ; Kim and Khang, 2014 ; Boulianne, 2015 ; Lee and Xenos, 2020 ), especially among the youth (Ida and Saud, 2020 ). In terms of focus and context of SMPP, studies have examined generalized forms of online political participation (Shehzad et al, 2021 ), and specific issues such as election (Dimitrova and Bystrom, 2013 ; Yang and DeHart, 2016 ), racism (Ince et al, 2017 ) and gender inequality (Quan-Haase et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, it raised people's interest and participation, and secondly, it reduced the direct and indirect communication gap between people and government (Balo & Shawon, 2018). People around the world use social networking applications such as Facebook to get the latest political news and information, which convert young voters into loyal voters (Somaiah, 2018), expanding access to social media increases political participation (Shehzad et al, 2021), active users of social networking sites are active participants of offline political activities, Political parties, candidates and political workers motivate voters to win elections, to enhance the legislative process and influence government policies (Aleyomi & Olanrewaju, 2014).…”
Section: Offline Political Participationmentioning
confidence: 99%